Lowering/Eliminating Learning Barriers in EFL Classrooms - Shrestha, Mallika Joshi (NELTA Bagmati Journal, 2022)
Language input does not get access to learners until and unless barriers are addressed beforehand, and effective delivery of input is the plan of any educational institution. This paper highlights five different learning barriers that students face at school and some practical ways to lower them. The article is based on the views collected through an interactive tool called Padlet and Google forms given to students and ‘focused group interactions’ with colleagues. It is based on my experiences in the field of teaching. It also includes some views on the causes of the barriers from related literature reviews. Barriers like boredom and anxiety could appear in all three stages of teaching. Some activities could be used to address more than one barrier.